2019
DOI: 10.4102/jir.v4i1.52
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus, physical activity, yoga and telomere length: A literature review

Abstract: Background: Type 2 diabetes mellitus (DM), a chronic metabolic disease prevalent in adults, is also prevalent amongst children, adolescents and young adults. On understanding the molecular basis of diabetes, a significant association is found between telomere length (TL) and type 2 DM.Aim: The aim of the study was to review the available evidence on effect of physical activity and yoga on DM including their effect on TL.Setting: The study was conducted in Bangalore.Method: A number of databases such as Google … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In contrast, previous studies have shown that controlling the consumption of fatty foods tends to reduce the risk of diabetes mellitus (42,43). The benefits of physical activity for diabetes mellitus have been reported in previous studies in both developed and developing countries (44)(45)(46). Physical activity can help reduce blood sugar levels in diabetics.…”
Section: Resultsmentioning
confidence: 86%
“…In contrast, previous studies have shown that controlling the consumption of fatty foods tends to reduce the risk of diabetes mellitus (42,43). The benefits of physical activity for diabetes mellitus have been reported in previous studies in both developed and developing countries (44)(45)(46). Physical activity can help reduce blood sugar levels in diabetics.…”
Section: Resultsmentioning
confidence: 86%
“…Yoga if practiced regularly and controlled can promote improvements in several indices that are very important in the management of DM2, including glycemic control, lipid levels, and body composition. Yoga can also lower oxidative stress and blood pressure, improve lung and nervous system function, improve mood, sleep, and quality of life, and reduce drug use in adults with DM2 (Ughreja & Ughreja, 2019). Doing yoga can reduce anxiety and as an adjunct therapy by type 2 diabetics to reduce long-term complications but must be done with the right duration to practice yoga the previous state must be relaxed because if the intervention is done Irregular eating allows no effect on glycemic control or other cardiovascular risks (Singh & Khandelwal, 2020).…”
Section: Discussionmentioning
confidence: 99%